2021
DOI: 10.1111/ina.12911
|View full text |Cite
|
Sign up to set email alerts
|

Emission rate of carbon dioxide while sleeping

Abstract: Humans emit carbon dioxide (CO2) as a product of their metabolism. Its concentration in buildings is used as a marker of ventilation rate (VR) and degree of mixing of supply air, and indoor air quality (IAQ). The CO2 emission rate (CER) may be used to estimate the ventilation rate. Many studies have measured CERs from subjects who were awake but little data are available from sleeping subjects and the present publication was intended to reduce this gap in knowledge. Seven females (29 ± 5 years old; BMI: 22.2 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…There have been a small number of recent studies in which measured CO 2 generation rates from humans have been compared with predictions based on Equation 4. The level of agreement between measurements and predictions is variable, but it should be noted that the predictions are highly dependent on the assumed value of M and that the sample sizes in these studies tend to be small 38,39 . All of the CO 2 generation rates in this paper are based on an air temperature of 296.15 K (23°C).…”
Section: Theory and Backgroundmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been a small number of recent studies in which measured CO 2 generation rates from humans have been compared with predictions based on Equation 4. The level of agreement between measurements and predictions is variable, but it should be noted that the predictions are highly dependent on the assumed value of M and that the sample sizes in these studies tend to be small 38,39 . All of the CO 2 generation rates in this paper are based on an air temperature of 296.15 K (23°C).…”
Section: Theory and Backgroundmentioning
confidence: 95%
“…The level of agreement between measurements and predictions is variable, but it should be noted that the predictions are highly dependent on the assumed value of M and that the sample sizes in these studies tend to be small. 38,39 All of the CO 2 generation rates in this paper are based on an air temperature of 296.15 K (23°C).…”
Section: Co 2 Generation From Building Occupantsmentioning
confidence: 99%
“…Humans emit CO 2 mainly through exhalation; dermal emissions could account for only up to 3.5% . The emission rate depends on the metabolic rate, sex, age, and environmental parameters. , Previous studies have reported per-person CO 2 emission rates for adults ranging from 11 L/h during sleeping to ∼80 L/h during physical activities. Humans can also emit NH 3 through exhalation. However, dermal emission is the dominating pathway of NH 3 emission, an order of magnitude larger than emission from breath. NH 3 emission rates range from 0.3 to 12 mg/h per person, depending on the age, clothing coverage, and air temperature. …”
Section: Introductionmentioning
confidence: 99%
“…Their impact on the CO 2 emission rates has been investigated experimentally in previous studies examining the effects of physical activity, 3–9 age, 8,10 and gender 4,8,9,11 . It has recently been shown that CO 2 emission rates can vary depending on other factors, including air temperature, 10,12–14 the concentration of CO 2 and other pollutants in the inhaled air, 14,15 and psychological effects 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Their impact on the CO 2 emission rates has been investigated experimentally in previous studies examining the effects of physical activity, [3][4][5][6][7][8][9] age, 8,10 and gender. 4,8,9,11 It has recently been shown that CO 2 emission rates can vary depending on other factors, including air temperature, 10,[12][13][14] the concentration of CO 2 and other pollutants in the inhaled air, 14,15 and psychological effects. 16,17 In a previous study, 14 we measured the CO 2 emission rates of six male volunteers who were seated, and therefore, at a low activity level and found that when elevated ambient CO 2 concentration (between 800 and 3000 ppm) was obtained either by restricting ventilation or dosing pure CO 2 from a gas cylinder, the CO 2 emission rate decreased.…”
Section: Introductionmentioning
confidence: 99%